Impact to the Valenzuela City Police Officers in the Implementation of Oplan Tokhang: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Tokhang is a Visayan word that means to approach and talk. “Oplan tokhang” is the campaignagainst illegal drugs in the country to improve peace and order. Oplan tokhang involves policevisiting the houses of individuals suspected to be involved in illegal drugs to persuade them tostop using drugs and submit themselves to authority for potential rehabilitation. This studyaimed to determine the impact of Oplan Tokhang in relation to the Police officer of ValenzuelaCity. To help them to lessen those problems they encountered and to pursue the campaignagainst illegal drugs.The findings of this study revealed how the Police officer may assess the impact of OplanTokhang in terms of security, psychological, and work status. Security and psychologicalavailability were interpreted as strongly Agreeable. and work status availability wasinterpreted as disagreeing.The assessment of the respondents on Oplan Tokhang was unsurprisingly blamed for thespate of extrajudicial killings, negative comments on social media, public criticism, and falseallegations by the community of the implementation of oplan tokhang. Some of the proposedrecommendations are based on the findings of problems encountered in the development andimplementation of Oplan Tokhang. The police officer may encourage more communityengagement to help bridge any apparent gaps between the police and the community andbuild a program to help the drug user have a new lifestyle. Philippine National Police shouldconduct regular seminars to pull them or tug them in the right direction, especially the victimsof these illegal drugs, and encourage the parents to voluntarily surrender their children whoare hooked on the drugs and undergo the government rehabilitation programs.
Keywords: Criminology